2006
DOI: 10.3390/11120940
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Synthesis of Molybdenum and Tungsten Tetracarbonyl Complexes with a Pyrazolylpyridine Ligand. Crystal structure of cis-[Mo(CO)4{ethyl[3-(2-pyridyl)-1-pyrazolyl]acetate}]

Abstract: Abstract:We report the one-step syntheses in good yields of the complexes cis-[M(CO) 4 (pzpy)] {M = Mo, W; pzpy = ethyl[3-(2-pyridyl)-1-pyrazolyl]acetate} directly from the corresponding M(CO) 6 starting materials by using microwave-assisted heating and reaction times of either 30 s (M = Mo) or 15 min (M = W). The structure of the molybdenum tetracarbonyl complex was determined by single crystal X-ray diffraction. The compound is monomeric and the molybdenum atom has a highly distorted octahedral geometry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Some of us recently became interested in the microwave-assisted synthesis (MAS) of metal-organic compounds [ 19 ]. Early studies on the use of MAS for metal carbonyl complexes of the type [M(CO) 4 (L) n ] (M = Cr, Mo, W) indicated that the reaction times could be reduced and the yields increased when compared to conventional methods which use, for example, oil bath heating [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of us recently became interested in the microwave-assisted synthesis (MAS) of metal-organic compounds [ 19 ]. Early studies on the use of MAS for metal carbonyl complexes of the type [M(CO) 4 (L) n ] (M = Cr, Mo, W) indicated that the reaction times could be reduced and the yields increased when compared to conventional methods which use, for example, oil bath heating [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…When performing the same reaction under microwave irradiation, reaction time was decreased to 1 min, and complexes 115 were recovered in 77−79% yield (Scheme 24). 84 cis-[Mo(CO) 4 (piperidine) 2 ] 117 106 and cis-[Mo-(CO) 4 (pzpy)] 118 107 (pzpy = ethyl[3-(2-pyridyl)-1pyrazolyl]acetate) were synthesized by reacting [Mo(CO) 6 ] under microwave irradiation with piperidine and pzpy 116, respectively (Scheme 25, reactions A, B, and C). Complexes were recovered in shorter reaction times and in higher yields than when obtained by synthesis in solution.…”
Section: Microwave Irradiation For the Synthesis Of Group 6 Metal Complexesmentioning
confidence: 99%
“…To solve this problem, Barnard and Leadbeater developed equipment for real-time monitoring of organometallic reactions under microwave irradiation using in situ Raman spectroscopy. 108 107 Incorporation of an organometallic functional group into a biomolecule to modify its properties has been developed recently. For instance, tungsten-containing pyrimidines such as metal complexes with mono-and dimethyl ureas, furnishing the heterocycles in high yields but in long reaction times.…”
Section: Microwave Irradiation For the Synthesis Of Group 6 Metal Complexesmentioning
confidence: 99%